2020
DOI: 10.3390/polym12092086
|View full text |Cite
|
Sign up to set email alerts
|

Designing Multifunctional Protective PVC Electrospun Fibers with Tunable Properties

Abstract: In this work, the electrospinning technique is used for the fabrication of electrospun functional fibers with desired properties in order to show a superhydrophobic behavior. With the aim to obtain a coating with the best properties, a design of experiments (DoE) has been performed by controlling several inputs operating parameters, such as applied voltage, flow rate, and precursor polymeric concentration. In this work, the reference substrate to be coated is the aluminum alloy (60661T6), whereas the polymeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Another interesting result is that an increase in the flow rate from 1000 µL/h up to 2200 µL/h produced an increase in the fiber diameter from 3.21 ± 0.11 µm (S1), 3.66 ± 0.21 µm (S3) up to 4.02 ± 0.13 µm (S5), respectively. This result was also in accordance with the literature because as the flow rate increased, the available polymer volume was higher, making possible an increase in the fiber diameter [49][50][51][52]. In addition, the effect of increasing the distance between the tip and collector resulted in the formation of thinner electrospun fibers from 3.95 ± 0.32 µm (10 cm, S6), 3.66 ± 0.21 µm (15 cm, S3) up to 3.32 ± 0.13 µm (20 cm, S7) which was in accordance with the literature [33,53].…”
Section: Surface Morphologysupporting
confidence: 92%
“…Another interesting result is that an increase in the flow rate from 1000 µL/h up to 2200 µL/h produced an increase in the fiber diameter from 3.21 ± 0.11 µm (S1), 3.66 ± 0.21 µm (S3) up to 4.02 ± 0.13 µm (S5), respectively. This result was also in accordance with the literature because as the flow rate increased, the available polymer volume was higher, making possible an increase in the fiber diameter [49][50][51][52]. In addition, the effect of increasing the distance between the tip and collector resulted in the formation of thinner electrospun fibers from 3.95 ± 0.32 µm (10 cm, S6), 3.66 ± 0.21 µm (15 cm, S3) up to 3.32 ± 0.13 µm (20 cm, S7) which was in accordance with the literature [33,53].…”
Section: Surface Morphologysupporting
confidence: 92%
“…An aspect to remark is that electrospun nano/microfibers deposited onto metallic substrates (aluminum, magnesium, steel) with intrinsic superhydrophobic or even highly hydrophobic behavior give long-term protection from corrosion [66]. In this sense, representative works can be found by using polyvinyl chloride (PVC) [67], polystyrene (PS) [68], poly(vinylidene fluoride) (PVDF) [69] or even perfluorinated block copolymer [70], among others. However, the use of metallic oxide nanoparticles combined with these synthetic hydrophobic polymeric precursors can be also employed as a novel approach to the development of highly anticorrosive surfaces.…”
Section: Corrosion Evaluationmentioning
confidence: 99%
“…Therefore, hydrophilic material, e.g., PVP, polyacrylonitrile (PAN), and poly(ethylene glycol) (PEG), can be added to PVC in order to reduce the water contact angle, which means that its hydrophobicity will be reduced [70][71][72]. It was found that when the number of particles in the nanofiber mat increased, it increased the roughness of the mat and eventually increased the water contact angle [73].…”
Section: Hydrophobicitymentioning
confidence: 99%
“…The results of anti-corrosion research showed that the aluminum surface significantly improved the resistance to pitting corrosion after being coated with PVC/ZnO nanofiber coating. In addition, Rivero et al [73] have proven that PVC nanofiber increases corrosion resistance through the Tafel polarization test.…”
Section: Protection From Corrosionmentioning
confidence: 99%